Analisis Penerapan Manajemen Operasional (Desain Produk dan Rantai Pasokan) Pada UKM Rotan Kelompok Pahari Palangka Raya - Sri Rohaetin, Intan Norrahmi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2020)
The method used in this research is descriptive method which is a method that aims to describe a problem clearly. The type of data used is primary data and secondary data. Data collection techniques consist of observation, interview and documentation. Data analysis was performed using qualitative data analysis techniques consisting of three stages of activities carried out sequentially namely reducing data, presenting data, and drawing conclusions. The results of this study indicate that the appropriate product design operational management to increase the sales results of the Pahari Palangka Raya Group Rattan UKM products is by applying eight aspects of product design (shape, features, performance, suitability, durability, reliability, style, and ease of repair) with priority on marketed products and prices. And in the proper supply chain operational management to increase the production output of the Pahari Palangkaraya Rattan Group UKM by implementing a strategy